Molecular mechanisms of RET receptor-mediated oncogenesis in multiple endocrine neoplasia 2 - Wagner, Simona M. (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2012)
Multiple endocrine neoplasia type 2 is an inherited cancer syndrome characterized by tumors of thyroid and adrenal tissues. Germline mutations of the REarranged during Transfection (RET) proto-oncogene, leading to its unregulated activation, are the underlying cause of this disease. Multiple endocrine neoplasia type 2 has been a model in clinical cancer genetics, demonstrating how knowledge of the genetic basis can shape the diagnosis and treatment of the disease. Here, we discuss the nature and effects of the most common recurrent mutations of RET found in multiple endocrine neoplasia type 2. Current understanding of the molecular mechanisms of RET mutations and how they alter the structure and function of the RET protein leading to its aberrant activation, and the effects on RET localization and signaling are described.